(untitled) (Northern International Medical College Journal, 2015)
Background : Acute viral encephalitis is a world-wide health problem with severe morbidity, significant mortality and a high incidence of residual sequelae in survivors. Objective : To identify the association of clinical features of acute viral encephalitis with mortality and neurodevelopment outcomes. Methodology : It is a hospital based comparative observational prospective study done in Dhaka Shishu Hospital during the period of October 2005 to March 2006. Children with 1 month to 12 years of both sex presenting with specific clinical features and laboratory evidences suggestive of acute viral encephalitis (seizures, altered consciousness, features of raised intracranial pressure, cerebrospinal fluid evidences of viral encephalitis) were included. 44 children were enrolled according to inclusion criteria. Data were collected on clinical and socio demographic status. SPSS 16 version program was used for data analysis. Result : Among the 44 cases, the mean age bellow 2 years was 14 months and above 2 years was 66 months. The incidence of acute viral encephalitis was highest within first 3 years of age. Most of the mortality 8(72.73%) occurred in low income group (P=0.003). 29(66 %) patients had Glasgow Coma Score <8 on admission, low Glasgow Coma Score at presentation had significant association with outcome, 11(100%) patients who died had Glasgow Coma Score <8(P=0.003). 28(68 %) patients stayed in hospital for >7 days, indicating more time taking for improvement from acute illness. There was significant association of duration of hospital stay and outcome (P=0.008). In Neurodevelopmental assessment domains were Gross motor, Fine motor, Vision, Hearing and Cognition and impairments were different in different patients. Impairments persisting in different domain at follow up comparing with admission showed satisfactory improvement. Improvement was significant in case of Gross motor (P=.005), Fine motor (P=.08) and Cognition (P=.09). Conclusion : It was observed from this study that children with acute viral encephalitis are at high risk of mortality and morbidity. Lower age at presentation, low socio-economic status, low Glasgow Coma Score on admission and short duration of hospital stay were associated with high mortality and were at high risk of future neurodevelopmental impairments Northern International Medical College Journal Vol.6(2) 2015: 50-52